1987
DOI: 10.1111/j.1600-0447.1987.tb02786.x
|View full text |Cite
|
Sign up to set email alerts
|

Major depression, parental mental disorder and early family relationships

Abstract: Sixty middle-aged urban women with a major depressive episode diagnosed in a community survey were compared with those 400 participants of the study who had no history of major depression. The study design is retrospective. The depressed women's parents had been in contact with psychiatric services twice as often as those of never depressed women. The rate of paternal alcoholism was however the same in both groups. As compared with the controls, women with major depression reported significantly more often fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…1980;Paykel, 1982). More recently, a broader range of influences has been considered, including severe adversity, such as parental mental illness and substance abuse, violence in the family and physical and sexual abuse of children (Hallstrom, 1987;Holmes & Robins, 1988;Mullen et al 1988;Kessler & Magee, 1993;Mathew et al 1993) and less extreme and even acceptable parental behaviour and disciplinary practices (Raskin et al 1971;Jacobson et al 1975;Perris et al 1986;Holmes & Robins, 1988). This shift in focus from traumatic events to enduring circumstances brought about a reevaluation of mechanisms involved in the observed associations between disorder, in child-hood or adulthood, and specific events such as parental divorce or death.…”
Section: Introductionmentioning
confidence: 99%
“…1980;Paykel, 1982). More recently, a broader range of influences has been considered, including severe adversity, such as parental mental illness and substance abuse, violence in the family and physical and sexual abuse of children (Hallstrom, 1987;Holmes & Robins, 1988;Mullen et al 1988;Kessler & Magee, 1993;Mathew et al 1993) and less extreme and even acceptable parental behaviour and disciplinary practices (Raskin et al 1971;Jacobson et al 1975;Perris et al 1986;Holmes & Robins, 1988). This shift in focus from traumatic events to enduring circumstances brought about a reevaluation of mechanisms involved in the observed associations between disorder, in child-hood or adulthood, and specific events such as parental divorce or death.…”
Section: Introductionmentioning
confidence: 99%
“…Sweden Accepted for publication March 2, 1999 Other studies have employed a multitude of measures of parenting, usually incorporated in structured or semi-structured interviews, but have reached comparable conclusions. In this context depression has been found to be associated with lack of warmth and with harsh discipline (7), parental antipathy, neglect and physical and sexual abuse (8, 9), harsh and unfair punishment (lo), parental rejection and lack of affection (1 l), frequent corporal punishment and feeling misunderstood by parents (12), and control through psychologically damaging techniques, such as withdrawal of affection and manipulation of guilt and anxiety (13). In a review of the literature it was concluded that the great majority of studies support the hypothesis that adverse child-rearing experiences are linked to adult depression (14).…”
Section: Stockholm Swedenmentioning
confidence: 99%